Pre-Hospital Care and Effect of Cardiopulmonary Resuscitation (CPR) On Survival Rate of Out-Of-Hospital Cardiac Arrest (OHCA) Victims, Telangana (India) - Husain, Amreen Aijaz; Rai, Uddipak; Sarkar, Amlan Kanti; V Chandrasekhar (National Journal of Community Medicine, 2024)
Introduction: OHCA is among the leading causes of mortality worldwide. India lacks a comprehensive database of cardiac arrests and an efficient emergency medical system. The treatment of cardiac disease has improved, yet the outcomes of OHCA remain poor. Methods: This is an observational 1-year prospective, single center, cohort study conducted on cohorts of OHCA victims. “Utstein Resuscitation Template” was followed for gathering the information starting location of arrest till the final resuscitation outcome. The information on OHCA patient treatment and current knowledge gaps is the aim of this study. Results: The study was conducted in the Warangal region of Telangana, India. The research comprised 1167 OHCA patients with a suspected cardiac etiology who were taken to the Mahatma Gandhi Memorial Hospital between June 1, 2022, and June 30, 2023. CPR attempts were recorded. Findings suggested if an individual was aware of the risk factors for CVD, they were more likely to report symptoms before OHCA. Conclusion: OHCA survival rate can be increased if the chain of survival is maintained by offering awareness and CPR training programs to the general public or bystanders, as well as efficient emergency ambulance services with qualified emergency medical staff.